Utilization of Cattle Manure Waste into Organic Fertilizer for Environmental Sustainability in Bojongsari, Purbalingga - Syarifah, Risqa Naila Khusna; Arum, Gadis Setya; Patimah, Popon; Athalloh, Akhmad Rizki; Candra, Celvin Febrian Edo Adi; Elvina, Ailsa Safa; Setiyaningrum, Dyah; Ungu, Septia Ayu Kencana; Saputri, Sela Nanda; Naomi, Arga Pratista; Setyaputri, Desvieta (Dharmahita: Journal of Community Service and Development, 2025)
Bojongsari Village is one of the villages in Bojongsari District, Purbalingga Regency. The livestock and agricultural sectors play an important role in the economy of Bojongsari Village. A total of 27 residents of Bojongsari Village own cattle, resulting in an increase in the amount of livestock manure produced. Poorly managed manure creates environmental pollution. One solution that can be applied to reduce this waste is by processing cow dung into solid organic fertilizer that can be reused by the community to support the agricultural sector. Therefore, the community service activity carried out in Bojongsari Village focused on training in the production of solid organic fertilizer from cow dung. The series of activities included coordination with Bojongsari Village officials, a survey of cattle pen locations, socialization and technical training on the production of solid organic fertilizer, as well as monitoring and evaluation. This program was positively received by local residents, especially farmer-livestock groups. Members of these groups gained new insights into the importance of managing livestock manure waste and obtained hands-on experience in making organic fertilizer. The resulting fertilizer can be used after undergoing a fermentation process for three weeks.